Integrated mobile phone shell capable of telescopically storing Bluetooth earphone - GAO XINYI; SUN WANG; YANG MEIZHEN; WANG ZHAOGUO; ZHANG XINGZI; LI DELONG; FENG YULE; LIANG YUANYUAN; YANG TINGHUA (2022)
The invention relates to the field of mobile phone shells, in particular to a telescopic storage mobile phone shell. The technical problem is that an existing mobile phone shell has few functions, and a user needs to carry an additional earphone storage device when going out. According to the technical scheme, the integrated mobile phone shell capable of telescopically storing the Bluetooth headset comprises an upper mobile phone shell body, a lower mobile phone shell body, a magnetic attraction block and the like, the lower mobile phone shell body is arranged on the right portion of the upper mobile phone shell body, and the upper mobile phone shell body makes contact with the lower mobile phone shell body; and the upper surface in the upper shell of the mobile phone shell is connected with a magnetic attraction block. According to the mobile phone shell, the function of replacing a Bluetooth headset storage device is achieved, a user can enjoy the convenience of Bluetooth headset storage when using the mobi